Phenolic compounds in leaves of Alchornea triplinervia: anatomical localization, mutagenicity, and antibacterial activity - Calvo, Tamara Regina [UNESP]; Demarco, Diego; Santos, Fabio V. [UNESP]; Moraes, Helen P. [UNESP]; Bauab, Tais M. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Colus, Ilce M. S.; Vilegas, Wagner [UNESP] (Natural Products Inc, 2010)
Phenolic compounds are produced by secretory idioblasts and hypodermis, and by specialized cells of the epidermis and chlorenchyma of leaves of Alchornea triplinervia. Phytochemical investigation of these leaves led to the isolation of the known substances quercetin, quercetin-7-O-beta-D-glucopyranoside, quercetin-3-O-beta-D-glucopyranoside, quercetin-3-O-beta-D-galactopyranoside, quercetin-3-O-alpha-L-arabinopyranoside, amentoflavone, brevifolin carboxylic acid, gallic acid, and methyl gallate from the methanolic extract, and stigmasterol, campesterol, sitosterol, lupeol, friedelan-3-ol, and friedelan-3-one from the chloroform extract. In studies of antibacterial activity and mutagenicity, the methanolic extract showed promising activity against Staphylococcus aureus (MIC=62.5 mu g/mL) and was slightly mutagenic in vitro and in vivo at the highest concentrations tested (1335 mg/kg b.w.).
Keywords: Alchornea triplinervia; flavonoids; antibacterial activity; mutagenicity; secretory structures